2002
DOI: 10.1046/j.1444-2906.2002.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of raw Spirulina platensis by larval tilapia Oreochromis niloticus

Abstract: Thirteen‐day‐old tilapia larvae (mean weight: 0.01 g), at the onset of exogenous feeding, were stocked at five fish per liter in rearing tanks. They were fed unialgal cultures of Spirulina platensis from varying ages [0, 12, 17, 21, and 28 days after the onset of exogenous feeding with a standard length (SL) of 0.8 cm, 1.8 cm, 2.0 cm, 2.5 cm, and 3.0 cm, respectively]. Feeding experiments on larvae fed different amounts of raw Spirulina were also designed. Acceptability tended to improve with an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…The results in the current study are in accordance with Watanabe et al (1990) and Takeuchi et al (2002) who found that feed supplemented with S. platensis powder improved the feed conversion ratio and growth rates in striped jack, Pseudocaranx dentex. Lu et al (2002) demonstrated that raw S. platensis can be an effective uni-feed for larval tilapia at a feeding rate of 30% (on a dry basis) of body weight. Abdel-Tawwab and Ahmed (2009) recorded that the growth and feed utilization of O. niloticus were obtained at 5.0 g fresh culture of S. platensis /kg diet.…”
Section: Discussionmentioning
confidence: 99%
“…The results in the current study are in accordance with Watanabe et al (1990) and Takeuchi et al (2002) who found that feed supplemented with S. platensis powder improved the feed conversion ratio and growth rates in striped jack, Pseudocaranx dentex. Lu et al (2002) demonstrated that raw S. platensis can be an effective uni-feed for larval tilapia at a feeding rate of 30% (on a dry basis) of body weight. Abdel-Tawwab and Ahmed (2009) recorded that the growth and feed utilization of O. niloticus were obtained at 5.0 g fresh culture of S. platensis /kg diet.…”
Section: Discussionmentioning
confidence: 99%
“…SP has been evaluated widely as fresh meal for mollusc bivalve and fish larvae (Harel et al, 2002;Lu et al, 2002) or as raw meal for juveniles and adults (Nandesha et al, 2001;Takeuki et al, 2002;Palmegiano et al, 2005;Palmegiano et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Arthrospira (Spirulina) platensis is an economically wellknown filamentous cyanobacterium that is commercially produced as a source of human health food (9), animal feed (31), and cosmetic colorants (11), and considerable efforts have been made to optimize the growth conditions of this organism for massive production (24,40,50,52). The morphological features of Arthrospira species include characteristic regular helical coiling or spirals.…”
mentioning
confidence: 99%